2012
DOI: 10.1177/0021998312454317
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal behaviours of polyetheretherketone-based multi-scale composites

Abstract: In this study, polyetheretherketone composites were compounded using a two-screw extruder followed by injection moulding. The effects of multi-fillers on the mechanical properties and crystallization performances were investigated. Differential scanning calorimetry results indicate that the addition of fillers slightly increases the crystallization temperature and crystallinity. Compared to neat polyetheretherketone, the incorporation of inorganic filler leads to a significant improvement in matrix hardness, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The strain at break of POM decreases by around 50% on the incorporation of 4 vol% CNTs. As is well known that the rigid fillers have contrast effects on the polymer matrix, however, they reinforced the matrix due to their high stiffness and strength, on the other hand, the presence of individual CNT and CNT agglomerates restricts the motion of molecular chains , and as a consequence, the ductility of the polymer matrix is decreased.…”
Section: Resultsmentioning
confidence: 99%
“…The strain at break of POM decreases by around 50% on the incorporation of 4 vol% CNTs. As is well known that the rigid fillers have contrast effects on the polymer matrix, however, they reinforced the matrix due to their high stiffness and strength, on the other hand, the presence of individual CNT and CNT agglomerates restricts the motion of molecular chains , and as a consequence, the ductility of the polymer matrix is decreased.…”
Section: Resultsmentioning
confidence: 99%
“…The comparison of a wrinkled area before and after tribological testing (Figure ) shows that the deformations can still be observed after the test and are not completely grinded away by wear. According to the work of Lin et al . the compression strain at yield is approximately 5%.…”
Section: Resultsmentioning
confidence: 99%
“…The material was compounded using a twin screw extruder, injection molded and welded on the substrate. The compound preparation as well as mechanical and thermal characterization has been described in detail by Lin et al . The composition of the compound is listed in Table .…”
Section: Methodsmentioning
confidence: 99%
“…PEEK when filled with inorganic materials like SCF, TiO 2 , ZnS, Graphite, SiO 2 leads to moderate increase in the crystalline structure of the composites, matrix hardness, stiffness and little increase in the tensile strength. Mechanical properties depend on the fiber orientation in the matrix [17]. It was found that frictional coefficient and specific wear are higher for dry condition than for water lubricated condition.…”
Section: Discussionmentioning
confidence: 99%